Message Sidedness in Health Claims: Roles of Mood State, Product Involvement, and Self-Rated Health Status - Lin, Hung-Chou; Wang, Shih-Tse (Frontiers in Nutrition, 2021)
Most of the previous studies regarding to message sidedness mainly focus on the effect of message sidedness in advertising on consumers＇behavior, it is unknown how consumers respond to different message sidedness when a one-sided or two-sided message in claims shown on the package of a healthy food product. The present research explores the underlying mechanisms how consumers respond to different message sidedness in claims. The results indicate that two-sided messages in claims are more persuasive than one-sided messages because they pass the “sufficiency threshold＂. In addition, the results of this article show that individuals＇mood state, product involvement and self-rated health moderate the relationship between message sidedness in claims and product evaluation.